Answer:
(2x-1)(2x+1)(x^2+2) = 0
Step-by-step explanation:
Here's a trick: Use a temporary substitution for x^2. Let p = x^2. Then 4x^4+7x^2-2=0 becomes 4p^2 + 7p - 2 = 0.
Find p using the quadratic formula: a = 4, b = 7 and c = -2. Then the discriminant is b^2-4ac, or (7)^2-4(4)(-2), or 49+32, or 81.
Then the roots are:
-7 plus or minus √81
p= --------------------------------
8
p = 2/8 = 1/4 and p = -16/8 = -2.
Recalling that p = x^2, we let p = x^2 = 1/4, finding that x = plus or minus 1/2. We cannot do quite the same thing with the factor p= -2 because the roots would be complex.
If x = 1/2 is a root, then 2x - 1 is a factor. If x = -1/2 is a root, then 2x+1 is a factor.
Let's multiply these two factors, (2x-1) and (2x+1), together, obtaining 4x^2 - 1. Let's divide this 4x^2 - 1 into 4x^4+7x^2-2=0. We get x^2+2 as quotient.
Then, 4x^4+7x^2-2=0 in factored form, is (2x-1)(2x+1)(x^2+2) = 0.
Answer:
Option B
Step-by-step explanation:
we have
we know that
<u>The vertical line test </u>is a visual way to determine if a curve is a function or not. A function can only have one value of y for each unique value of x
In this problem
The given function passes the vertical line test
therefore
f(x) is a function
<u>The Horizontal Line Test</u> is a test use to determine if a function is one-to-one
If a horizontal line intersects a function's graph more than once, then the function is not one-to-one.
In this problem
The given function fails the horizontal line test
because for f(x)=0 x=-3, x=-1, x=3
therefore
It is no a one-to-one function
Answer:
(x, x2 − 3x − 28) for all real numbers
Step-by-step explanation:
Answer:
x=1 and x=3
Step-by-step explanation:
let : f(x) = 2^x−8 and g(x) = 3x−9
the graph of g color red and the graph of f color bleue
the solutions are 1 and 3